Experiência Óptima e Cortisol: A Psicofisiologia no Quotidiano - Matias, Gabriela P. (2009)
Positive Psychology aims to understand and develop the individual qualities and strengths that promote optimal quality of life. The individual will express and develop his/her abilities and personal life theme according to his/her subjective experiences in daily life. The Experience Fluctuation Model (EFM) explains the variation in subjective experience according to the individual perception of challenges and skills, which is translated into eight channels which differ in the affective tonus and in the degree of psychic and physical arousal. This article’s aim is to explore the connections between physiology and concepts explored by Positive Psychology through the review of some of the present literature, to understand how this model can express distinct physiological states depending on the individual’s subjective experience and how daily life can reflect or be a reflex of psychosocial states and its physiological correlates.